The effect of the Raigluth model using multimedia on learning passing skills and scoring futsal for female students (Journal of Humanities and Social Sciences Research, 2023)
Passing and scoring skills are among the most significant basic skills in the futsal game, which serve as the foundation for establishing performance levels, and so promote competent performance in futsal. In this case, the researcher worked to support the learning process by using an educational model (Ragilot) with multimedia based on the model's stages in order to build the learning process on foundations that contribute to simplifying, facilitating, and improving the quality of learning among students. The researcher attempted to include special activities in mastering the skills of passing and scoring in futsal. Additionally, determine the extent to which learning both abilities and achieving the optimal level will achieve the researcher's research aim. The results revealed that the activities in this manner have an influence on the stage students' development of passing and scoring skills in the futsal game.